CADCAM Versus Conventional Denture Bases: Network Meta-Analysis of In Vitro Studies Comparing Accuracy and Surface Properties - Rohit Kunnath Menon; Yew Hui Xin; Benjamin Chen Tze Wei; Sarah Omar AlSaqaf; Adonis Khaled Abu Kariem; Maram Mohamad Al Tabbaa; Sajesh K. Veettil (International Dental Journal)
Introduction: This systematic review with network meta-analysis (NMA) analysed the current evidence on in vitro studies comparing trueness of fit, surface roughness, colour stability, surface wettability, water sorption, water solubility, and microbial adhesion between conventional and digital denture bases. Methods: From inception until December 2023, a systematic search of published in-vitro studies from Scopus, PubMed, and the Cochrane Central Register of Controlled Studies was conducted. The protocol was registered in PROSPERO (CRD42024531416). NMA compared properties related to dimensional accuracy and surface properties between conventional and digital dentures. The ranking was performed using the surface area under the cumulative ranking guidelines. Results: A total of 6004 articles were initially identified, of which 342 duplicates were removed, and 5566 were excluded by screening the titles and abstracts. A total of 96 articles were assessed by full-text reading, and 43 were included in the quantitative synthesis. As per the NMA results, MIL demonstrated significantly higher trueness of fit when compared with conventional compression moulding (standardized mean differences [SMD] = –2.25 [95% CI: –4.09, –0.40]), P = .017 (<.05) and TDP (SMD = –1.57 [95%CI: –3.14, –0.01]) P < .05. MIL demonstrated significantly lower surface roughness when compared with conventional compression moulding (SMD = –0.99 [95% CI: –1.72, –0.26]), P = .008 (<.05), and TDP (SMD = –1.08 [95%CI: –1.95, –0.22]) P < .05. Conclusions: There is conclusive evidence that milled digital denture bases demonstrate higher trueness of fit and lower surface roughness than 3D-printed denture bases and conventional denture bases, as demonstrated by the concurrent network and pairwise results. Clinical Relevance: In vitro studies show that milled digital dentures exhibit higher accuracy and lower surface roughness. The clinical performance of milled dentures in relation to these properties needs to be evaluated by high-quality randomized controlled clinical trials.